Strategi Bisnis Bagi Hasil Ternak Kambing Dari Fase Kehamilan"Studi Kasus Desa Tapango Barat Kecamatan Tapango - Burhanuddin , Burhanuddin; Alwi , Muhammad; Ramayani, Indah (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The analysis method used in this study is qualitative descriptive analysis with a case study approach to describe the practice of the sharecropping system for pregnant goats in Tapango Barat Village, Tapango District, Polewali Mandar Regency. This study aims to understand how the sharecropping system, based on local wisdom, works by relying on trust and social solidarity between goat owners and livestock managers. Data was collected through observation and in-depth interviews with goat owners, livestock managers, and local community leaders. The research findings show that this sharecropping system consists of three main models: equal profit-sharing, giving the first goat kid to the investor, and giving the first goat kid to the manager. Despite the absence of formal contracts, this practice operates effectively due to strong social relationships and trust values prevalent in the community. Additionally, the system maintains social balance and avoids inequalities in profit distribution. This study links the sharecropping system with Granovetter’s concept of embedded economy and Scott’s moral economy, which emphasize the importance of social relationships and justice in traditional economic activities. Overall, this study shows that the community-based economic practice in Tapango Barat Village is a sustainable economic model, which can serve as an example for other regions to create fairer welfare based on local wisdom.